Korelasi Persepsi terhadap Kebutuhan Fisioterapi Antenatal untuk Mengatasi Masalah Muskuloskeletal Ibu Hamil - Roikhatul Jannah; Dwi Agustina; Windya Puspa Faradisa (Politeknik Kesehatan Kemenkes RI Jakarta I, 2019)
The changes of hormone and anatomy results in musculoskeletal problem in pregnant women. Physiotherapy plays important role during pregnancy. However, in Indonesia, the number of attendants to antenatal physiotherapy was limited. This was thought to be associated to the perception of pregnant women toward the need of services. The present study aims to determine the factors related to pregnant womenâ€™s perception towards need of antenatal physiotherapy services in Puskesmas Kecamatan Cipayung. Target population of this cross sectional study was all pregnant women in Puskesmas Kecamatan Cipayung among 103 participants who purposively selected were interview. Analysis data using univariate and bivariate analysis (Chi Square test). The majoririty of education level, working status, and income level were respectivelly senior high school (61.2%), unemployee (82.5%), and Rp2.500.000-3.500.000 (37.9%). Furthermore, most of respondents complain on musculoskeletal disorder especially low back pain, namelly (63.1%) while their lack of knowledge on physiotherapy was 70.9%, and perception towards the need of antenatal physiotherapy service with indicator â€œno needâ€?? was counted 52,4%. p value between perception toward need of antenatal physiotherapy with education, income, knowledge level and working status were p=0.041, p=0.001, p=0.000, and p=0.314. Results reveal that education level, income level, and knowledge were significant factors affecting pregnant womenâ€™s perception towards antenatal physiotherapy services meanwhile working status was not significant.It is recommended to promote physiotherapy services for better play role on women health improvement.